(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
Paper presents results of the analysis of possible design solutions of timber beam bridges considering all usual demands for their stability, safety and functionality when they are designed to serve pedestrian and cyclist traffic, and, if necessary, traffic of emergency and service vehicles as well. Parametric finite element models (FEM) of bridges with simply supported glulam main-beams, have been divided into four groups, each consisting of several subgroups. The type of load-carrying deck (solid timber or CLT deck, covered by asphalt layer and protected) and its position (lower or upper) were selected as relevant characteristic for some group, while the type of transverse layout, corresponding to certain deck width and usable traffic profile, and also accompanying solution of spatial stabilization were decisive for differentiation of considered subgroups. Using the span of the straight main-beams and useful width of the load-carrying deck, conditioned by traffic requirements as input parameters, prepared FE models, classified into twelve different cases were undergone to static and dynamic analyses. According to criteria we selected as relevant, the results of performed analysis were given as recommendations for the selection of optimal structural layout matching the span of the bridge and the requests on its functionality and durability.